Occupational Stress, Leadership Style, and Turnover Intention among Private School Teachers in Kathmandu Valley - Subedi, Dhruba Prasad; Khanal, Kapil (Nepalese Journal of Management and Technology, 2025)
This study investigates the relationship between occupational stress and turnover intention among private school teachers in the Kathmandu Valley, with a particular focus on the moderating effect of leadership style. Teaching in private institutions often involves high workloads, low job security, and pressure to meet performance standards, leading to increased stress levels and the possibility of teacher turnover. Using a structured questionnaire, data were collected from 300 private school teachers and analyzed using correlation and moderation analysis. The results indicate that occupational stress has a significant and positive impact on turnover intention, suggesting that higher stress levels increase the likelihood of teachers intending to leave their jobs. Furthermore, the findings reveal that leadership style significantly moderates this relationship. Specifically, transformational leadership was found to weaken the positive link between occupational stress and turnover intention, indicating that supportive and inspiring leadership can buffer the negative effects of stress. These findings emphasize the importance of effective leadership in managing occupational stress and retaining teaching staff. The study offers practical implications for school administrators and policymakers to foster healthier work environments and adopt leadership approaches that reduce stress and enhance teacher retention in private educational institutions.